Physics and operation oriented activities in preparation of the JT-60SA tokamak exploitation. (12th July 2017) - Giruzzi, G.; Yoshida, M.; Artaud, J.F.; Asztalos, Ö.; Barbato, E.; Bettini, P.; Bierwage, A.; Boboc, A.; Bolzonella, T.; Clement-Lorenzo, S.; Coda, S.; Cruz, N.; et al.
Abstract: The JT-60SA tokamak, being built under the Broader Approach agreement jointly by Europe and Japan, is due to start operation in 2020 and is expected to give substantial contributions to both ITER and DEMO scenario optimisation. A broad set of preparation activities for an efficient start of the experiments on JT-60SA is being carried out, involving elaboration of the Research Plan, advanced modelling in various domains, feasibility and conception studies of diagnostics and other sub-systems in connection with the priorities of the scientific programme, development and validation of operation tools. The logic and coherence of this approach, as well as the most significant results of the main activities undertaken are presented and summarised.